Development of Graphical User Interface (GUI) Platform for Sizing A Grid-Connected Photovoltaic (PV) System - Mohd Nordin, Ahmad Syahmi; Mohamad Nor, Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2020)
The research presented in this project focuses on the development of a Graphical User Interface (GUI) platform for sizing a grid-connected Photovoltaic (PV) System. The GUI is designed to have the capability to sizing the load consumption and determine the usage of every component for the grid-connected PV system, costing and return on investment (ROI). System sizing is vital because to ensure all the equipment that is used not producing extra energy needed which related to the costing and ROI. This GUI can show all the procedures system sizing from load consumption until the return on investment of the single-storey terrace house. The GUI is created by using the MATLAB Software application, which is GUIDE. The generated result from GUI application needs to correspond with the manual calculation to ensure the process of sizing the grid-connected PV system can be used for this project. Hence, it is important to do the correct sizing because the total payback period depends on total monthly saving and total cost of the PV system installation.